2004
DOI: 10.1128/aac.48.10.3749-3757.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Composition and Decreased Autolytic Activity and Lysostaphin Susceptibility of Glycopeptide-Intermediate Staphylococcus aureus

Abstract: The cell wall composition and autolytic properties of passage-selected glycopeptide-intermediate Staphylococcus aureus (GISA) isolates and their parent strains were studied in order to investigate the mechanism of decreased vancomycin susceptibility. GISA had relatively modest changes in peptidoglycan composition involving peptidoglycan interpeptide bridges and somewhat decreased cross-linking compared to that of parent strains. The cell wall phosphorus content of GISA strains was lower than that of susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 56 publications
(87 reference statements)
3
80
1
Order By: Relevance
“…Reduced autolytic activity is a common feature of hVISA and VISA strains and is a common early phenotypic change in serial isolates obtained during persistent infection (30,31,108,160), although this has not been demonstrated for all isolates (121). Initial studies of Japanese VISA strain Mu50 reported an increase in autolytic activity (362); however, recent data have confirmed that Mu50 demonstrates reduced whole-cell autolytic activity like other VISA strains (362).…”
Section: Autolytic Activitymentioning
confidence: 87%
See 2 more Smart Citations
“…Reduced autolytic activity is a common feature of hVISA and VISA strains and is a common early phenotypic change in serial isolates obtained during persistent infection (30,31,108,160), although this has not been demonstrated for all isolates (121). Initial studies of Japanese VISA strain Mu50 reported an increase in autolytic activity (362); however, recent data have confirmed that Mu50 demonstrates reduced whole-cell autolytic activity like other VISA strains (362).…”
Section: Autolytic Activitymentioning
confidence: 87%
“…Initial studies of Japanese VISA strain Mu50 reported an increase in autolytic activity (362); however, recent data have confirmed that Mu50 demonstrates reduced whole-cell autolytic activity like other VISA strains (362). Some data suggest a possible role for wall teichoic acids of VISA strains suppressing peptidoglycan degradation by autolytic enzymes (318), while other studies suggested that a reduction in the autolytic activity and altered peptidoglycan hydrolase activity of VISA autolysin extracts are responsible for the reduced autolytic activity (160). It was proposed that vancomycin binding in the staphylococcal cell wall directly blocks the activity of a peptidoglycan hydrolase and explains the reduced autolytic activity demonstrated in the presence of vancomycin (321); however, this does not explain the reduced autolytic activity of hVISA and VISA strains in the absence of vancomycin (121).…”
Section: Autolytic Activitymentioning
confidence: 88%
See 1 more Smart Citation
“…After gels were washed, they were placed in 50 ml of Tris buffer and incubated at 37°C for 15 h. For visualization of protease clearing zones, gels were stained with Coomassie brilliant blue. Autolysin (murein hydrolase) zymography was performed as described previously (42). Cell cultures were grown, and supernatants were prepared and concentrated as described above.…”
Section: Mapping Transposon Insertionsmentioning
confidence: 99%
“…Daptomycin exerts its bactericidal effects by binding to the bacterial cell membrane, resulting in efflux of potassium ions into the cell and subsequent cell death (2,17,18). Vancomycin exerts its activity on the cell wall (6,7). GISA strains demonstrate thicker cell walls with binding sites that sequester the drug (4,6,15).…”
mentioning
confidence: 99%